Acting out antiquity: representations of the Classical world in early American Theatre, 1732-1831 - Fisher, Gary F. (2020)
This thesis explores how the ancient world was represented on the American stage from 1732 to 1831. These two years mark the first recorded instance in which the ancient world was depicted on an Anglophone American stage in 1732, and the eventual premiere of what would become the first American-written play representing the classical world to experience runaway success in 1831. Prior studies in the American tradition of acting out antiquity have relied primarily on case studies and close readings as investigative tools. This thesis examines the period holistically, examining how Americans engaged with antiquity on stage from that first performance of Joseph Addison’s Cato, A Tragedy (1713) in 1732 to the release of Robert Montgomery Bird’s The Gladiator (1831). In this endeavour, this thesis deploys a novel, comprehensive approach that combines statistical analysis, periodized historical analysis, and close readings of key texts. By analysing the results of a large-scale data-collection exercise, it models the relative frequencies with which different texts were performed across different time periods, regions, and performance contexts. In doing so, this thesis identifies numerous hitherto forgotten plays that defined American audiences’ experience of the Classics on stage, and maps out the wider cultural landscape in which they existed. After a first chapter outlining and analysing the results of this data collection exercise, four diachronic chapters trace the emergence of a distinctly American dramatic interpretation of the Classics over the course of this century. Within each of these chapters is embedded a close reading of one of the most significant dramatic texts of the period in question. Through this mutually-informed combination of large-scale data analysis, periodized historical analysis, and detailed close readings of individual texts, this thesis not only offers a history of this particular species of the Classics’ reception in the New World, but also a new approach to classical reception studies.